Correlations between economically useful traits of bees of different breeding crosses of the Carpathian breed - M. S. Stetsyshyn; V. V. Fedorovych; Ye. I. Fedorovych (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
Establishing correlations between bee breeding traits is of great theoretical and practical importance for the beekeeping industry. With the help of correlation coefficients, breeders can randomly select a desired trait, considering how it is related to other breeding traits. This, in turn, makes it possible to predict the productive qualities of bees. Therefore, our research aimed to study the relative variability of economically valuable traits of bees of different breeding crosses of the Carpathian breed. The studies were conducted on bees of different genealogical formations of the Carpathian breed in private apiaries in Navariya village, Lviv region. For experimental studies, 6 groups of 10 bee colonies were formed in each group: I – the control group – bees of the Carpathian population of the Vuchkovsky type; II – inbred group ♀ microline ‘915’ x ♂ microline ‘915’; III – breeding cross ♀ microline ‘Sto’ x ♂ microline ‘915’; IV – breeding cross ♀ type ‘Vuchkovsky’ x ♂ microline ‘915’; V – breeding cross ♀ microline ‘67’ x ♂ microline ‘915’; VI – breeding cross ♀ microline ‘07’ x ♂ microline ‘915’. To determine the presence, direction, and degree of relationships between economically beneficial traits of bees, we used correlation analysis using the software package STATISTICA 6.1. The results of our research indicate that there are multidirectional and different strengths of relationships between bee breeding traits. Correlation coefficients between honey productivity and bee colony strength ranged from -0.16 to +0.45, queen egg production from -0.03 to +0.68, hygienic behavior of bees from -0.22 to +0.47, flight activity of bees from -0.04 to +0.36, proboscis length from -0.21 – +0.85, forewing length – in the range of -0.05 – +0.44, feather productivity – in the range of 0.03 – +0.18, wax productivity – in the range of -0.02 – +0.39 and propolis productivity – in the range of -0.06 – +0.55. Relationships between wax productivity and wax mirror length, depending on the cross, ranged from -0.51 to +0.32, wax mirror width – from -0.24 to +0.50, bee colony strength – from -0.43 to +0.55, number of closed brood – from -0.27 to +0.34, propolis productivity – from -0.08 to +0.50 and feather productivity – from -0.10 to +0.32. Multidirectional and different strengths of correlations were observed between the hygienic behavior of bees and their propolis productivity and pollen collection activity, as well as between the flight activity of bees and propolis productivity and pollen collection activity. Thus, the relationships between the economically beneficial traits of bees of the controlled breeding crosses of the Carpathian breed were multivector and ranged from weak to high and reliable to unreliable.